Proceedings of the International Conference on Signal, Networks, Computing, and Systems ICSNCS 2016, Volume 2 - Lobiyal, Daya K.; Mohapatra, Durga Prasad; Nagar, Atulya; Sahoo, Manmath N.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The book is a collection of high-quality peer-reviewed research papers presented in the first International Conference on Signal, Networks, Computing, and Systems (ICSNCS 2016) held at Jawaharlal Nehru University, New Delhi, India during February 25-27, 2016. The book is organized in to two volumes and primarily focuses on theory and applications in the broad areas of communication technology, computer science and information security. The book aims to bring together the latest scientific research works of academic scientists, professors, research scholars and students in the areas of signal, networks, computing and systems detailing the practical challenges encountered and the solutions adopted.
Part 1. Advanced Computing Paradigm: Chapter 1. Interactions with Human CD4 Protein Leads to Helix-to-Coil Transition in HIV-gp120 Aiding CCR5 Attachment and Viral Entry: An In silico Structural Biology Approach for AIDS -- Chapter 2. A Support Vector Machine approach for LTP Using Amino Acid Composition -- Chapter 3. Load Balancing Challenges in Cloud Computing: A Survey -- Chapter 4. Physiological Modeling of Retinal Layers for Detecting the Level of Perception of People with Night Blindness -- Chapter 5. An Improved Encryption and Signature Verification ECC Scheme for Cloud Computing -- Chapter 6. Implementing a Web-based Simulator with Explicit Neuron and Synapse Models to Aid Experimental Neuroscience and Theoretical Biophysics Education -- Chapter 7. On Intuitionistic Fuzzy Soft Sets and Their Application in Decision Making -- Chapter 8. CheckPDF: Check What is Inside Before Signing a PDF Document -- Chapter 9. Kinematic Analysis of a Two Wheeled Self-balancing Mobile Robot -- Chapter 10. Program Code Understandability and Authenticating Code Predicting Systems: A Metric Based Approach -- Chapter 11. Fuzzy Sliding Mode Based STATCOM for Stability and Reactive Power Compensation in DG Based Power System -- Chapter 12. ANFIS Based Controller for DFIG Based Tidal Current Turbine to Improve System Stability -- Chapter 13. Design of Reversible Floating Point Adder for DSP Applications -- Chapter 14. Navigation of Mobile Robot Using Type-2 FLC -- Chapter 15. Analysis of the Complexity of Brain under Mobile Phone Radiation Using Largest Lyapunov Exponent -- Chapter 16. A Review of Bio Inspired Computing Methods and Potential Applications -- Chapter 17. An Effective Task Scheduling Approach for Cloud Computing Environment -- Chapter 18. Construct Based Sentiment Analysis Model -- Part 2. Methodologies for Systems Design: Chapter 19. Effect of Delay Approximation Using Pade Technique on Controller Performance Designed for a SOPDT Model -- Chapter 20. Neuro-Fuzzy Controller Design for MIMO Boiler Turbine Process -- Chapter 21. Predictive Control System Design for Lime Kiln Process -- Chapter 22. Design of Time Delay Compensator for a FOPDT Process Model -- Chapter 23. A Concept for Test Case Prioritization Based Upon the Priority Information of Early Phase -- Chapter 24. MEMS Based Phase Shifters for Phased Array Applications Fully Integrated on PCB Substrates -- Chapter 25. A Novel Multipath Mitigation Technique for SPSGPS Receivers in Indian Urban Canyons -- Chapter 26. Controller design for a TOPDT Process Model Using Integral Error Based Tuning Techniques -- Chapter 27. Effect of Variation in Filter Co-efficient for Different PID Controller Structures on Performance of SOPDT Process -- Chapter 28. Controller Capability Comparison for a Delayed First Order ProcessModel -- Chapter 29. Optimization Study on Quarter Car Suspension System by RSM and Taguchi -- Chapter 30. On Modeling and Analysis of Launch Vehicle System -- Chapter 31. Performance Evaluation of Tree-Based Classification Techniques on Intrusion Dataset -- Chapter 32. Kinematic Modeling and Simulation of 3-Axis Robotic Arm for Performing Welding Operations with Arbitrary Weld Joint Profiles -- Chapter 33. Modeling and Simulation for Conductivity of Germanium and YBCO -- Chapter 34. Cryptoviral Extortion: Evolution, Scenarios and Analysis -- Chapter 35. Utilization of Fractal Geometry for Phase Shifter Implementation -- Chapter 36. Simulation Studies for Delay Effect on Stability of a Canonical Tank Process -- Chapter 37. Current Signature Analysis of Single Phase ZSI Fed Induction Motor Drive System -- Chapter 38. Kinematic Control of a Mobile Manipulator.
Keywords: Telecommunication; Signal processing; Computer networks .; Communications Engineering, Networks; Signal, Speech and Image Processing; Computer Communication Networks